Predicting the Equilibrium Product Formation in Oxy-fuel Combustion of Octane (C8H18) using Numerical Modeling - Bargos, Fabiano Fernandes; Romao, Estaner Claro (Engineering, Technology & Applied Science Research, 2023)
Preserving the environment is a major challenge for modern society, and reducing the greenhouse effect caused by combustion processes is a primary concern. It is known that nitrogen compounds (NOx) negatively impact air quality and public health. Internal combustion engines, responsible for nearly half of the atmosphere’s pollutants, have prompted public policymakers to phase out gasoline and diesel-powered vehicles in the near future. Carbon capture and storage technologies, including oxy-fuel combustion, are being developed to address these environmental challenges. To predict exhaust pollutants such as NO and CO, assuming that the exhaust gases resulting from fuel and air combustion are in chemical equilibrium is a useful approximation. In the current case study, a numerical investigation on the impact of modifying the oxygen content of the reaction mixture from 21% to 100% on the equilibrium composition of C8H18 air-enriched combustion was conducted. Specifically, the equilibrium-constant approach routines were tailored for 10 species reported in the literature to the conditions of oxy-fuel combustion. Additionally, a comprehensive analysis was performed by varying the temperature and equivalence ratio alongside the oxygen level. The results emphasize the intricate interplay between various factors in oxy-combustion and provide valuable insight into the equilibrium product formation in oxy-fuel combustion. Notably, the non-uniform reduction of N2 as a function of O2 is highlighted, with an overall reduction rate of 0.93 observed across the range of O2 percentages from 21% to 99%.